PERMINTAAN WISATA ALAM DI KAWASAN PELESTARIAN ALAM DI BOGOR - Muharmansyah .; E.K.S Harini Muntasib; Eva Rachmawati (Media Konservasi, 2012)
Information on tourist demand is an important key in planning the management and development of nature tourism area.  The research was aimed at identifying nature tourism demand in national park (NP) and nature tourism park (NTP) in Bogor.  Data was collected through literature study and questionnaires dissemination to 102 respondents of NP and NTP visitors.  Result showed that there were differences between the demand of NP and NTP visitors on the characteristic of dominant age group, visiting reasons, demand of activity and facilities, visiting time, and type of visitor based on their visit to the location (repeater or first timer). Visitors of NP and NTP in Bogor were dominated by domestic tourist from Jabotabek region, and the highest number visitors were male.   Keywords: demand, tourist, national park, nature tourism park, Bogor.